Combination of Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) and Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA) in Determining the Best Cashier - Sintaro, Sanriomi; Aldino, Ahmad Ari; Setiawansyah, Setiawansyah; Saputra, Very Hendra (Journal of Computing and Informatics Research, 2023)
MOORA (Multi-Objective Optimization by Ratio Analysis) method is one of the multi-criteria analysis techniques used for alternative selection based on several different criteria or objectives. In the context of selecting the best cashier, by using the MOORA method to select cashiers based on several relevant criteria. While Pivot Pairwise Relative Criteria Importance Assessment (PIPRECIA) is a method used to assess the importance of criteria relative to each other in the context of multi-criteria analysis. This method helps in determining the weight of criteria used in multi-criteria decision making. The combination of MOORA and PIPRECIA will produce the best cashier selection based on the criteria used. The results of the best cashier assessment ranking using the Multi-Objective Optimization method on the basis of Ratio Analysis (MOORA) and the Simplified Pivot Pairwise Relative Criteria Importance Assessment weighting method obtained results, namely for Rank 1 obtained by Rini Maya with a final value of 0.343.